PENGARUH DIFERENSIASI PRODUK, DIFERENSIASI PELAYANAN, DIFERENSIASI PERSONALIADAN DIFERENSIASI CITRA TERHADAP KEPUTUSAN PEMBELIAAN SEPEDA MOTOR HONDA BEATPADA CV. MINA SPN MOTOR DI KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Marina, Hesti; Masrin, SE, MM, Indra; Utami,SE, MBA, HayuYolanda (Pendidikan Ekonomi, 2014)
ABSTRACTThis study aimed to reveal the effect of : product differentiation on the purchase decisions of Honda motorcycles Beat on the cv. Mina SPN Motor in District Valley Crossing West Pasaman , service differentiation influence on purchasing decisions motorcycle Honda Beat on the cv . Mina SPN Motor Â in District Valley Crossing West Pasaman , influence purchasing decisions terhadapa differentiation personnel Honda Beat on the cv. m in District Valley Crossing West Pasaman , image differentiation influence on purchasing decisions motorcycle Honda Beat on the cv . Mina SPN Motor in District Valley Crossing West Pasaman .This type of research conducted in this study is descriptive Associative . The population in this study is people in the District Valley Crossing West Pasaman sex men and women between the ages of 17-29 Year who know information about Honda motorcycles Beat the sampling area ( area probability sample ) , the number of 95 people .Data were collected through a questionnaire using a Likert scale that has been tested reliability The data analysis technique used is descriptive analysis . To test the hypothesis used by t test and f test . based on the results of t-test of hypothesis testing berpengauh product differentiation positive and significant impact on purchasing decisions , service differentiation t test positive and significant impact on purchasing decisions , personnel differentiation t test positive and significant impact on purchasing decisions and differentiation of T test image and a significant positive effect on the decision purchase . The magnitude of the effect of product differentiation , service , personnel , image on consumer purchasing decisions is 23.80 % and the remaining 77.20 % is influenced by other variables not included in the research model.